(untitled) (Research, Society and Development, 2020)
The records of products with a geographical indication (GI) are produced in regions where it is possible to identify certain differentials, which are related to the place and form of production, soils, climate, and harvest. One type of GI is the Denomination of Origin (DO), which refers to the geographical name of the region that has unique qualities and characteristics, including natural and human factors, which, materialized in the product produced there, differentiate it from the others. Thus, this study aimed to delimit the geographical area of the DO yerba-mate of Planalto Norte Catarinense (PNC), since its contribution to the region is of great economic, social and environmental importance. The geographical delimitation of the area was carried out, which was based on the crossing of the Political Map, Hydrography Map, the digital terrain model, the historical evolution of the municipal limits and the location of the producers of yerba mate. The structuring of the IG of PNC for mate products seeks not only the formalization and the achievement of a certificate of registration of an IG, but also the effective participation of the actors in the production chain, in decision-making, in making public policies feasible, and the construction of collective agreements. The geographical delimitation allowed to define the production area that allows obtaining a specific quality product. The geographical delimitation area of the IG yerba mate of the PNC corresponds to 12,024.81km2, representing 12.6% of the Santa Catarina territory. The IG is gaining notorious importance in the agro-industrial market because it has the competence to differentiate a product or service from its peers, based on natural characteristics (climate, soil, vegetation) and human characteristics (way of doing), thus making it a unique product.